Revelation, truth, canon and interpretation: studies in Justin Martyr's Dialogue with Trypho - Allert, Craig D. (2001)
Revelation, Truth, Canon, and Interpretation are four fundamental issues in pre-Nicene Christianity. This dissertation seeks to examine these in Justin Martyr's Dialogue with Trypho. The INTRODUCTION indicates the impetus for this investigation and reviews the pertinent secondary sources and their contributions to these issues. A review of Justin's life and his extant writings is also included. CHAPTER ONE examines Justin's concept of Revelation. Justin's conversion to Christianity is placed in the context of his Middle Platonism. From this context we learn that, as a philosopher, Justin's primary goal was knowledge of God. The case Justin builds throughout the Dialogue is that the true philosophy, the incarnate Logos, is witnessed to only in the Prophets and the Apostles. The incarnate Logos is seen as the culmination in God's plan for salvation and is thus revelation. CHAPTER TWO examines Justin's concept of truth. From the genre that Justin chose and his understanding of the attainment of truth as the goal of a philosopher, we see that Justin saw truth as located in the Logos. Justin is differentiated from the Hebrew and the Platonic concepts of truth and continues the line of argument established in the NT writers. Truth is fulfilled and found in Jesus Christ, through his pre-existence and his incarnation. CHAPTER THREE examines Justin's concept of canon. Justin did not conceive of a closed collection of Christian writings. While his references to Memoirs are important, they should not be seen as implying a closed collection of Christian writings. Concerns about this belong to an age later than Justin's. CHAPTER FOUR highlights the foundations upon which Justin interpreted the Hebrew scriptures. The determining factor here is the new Covenant which was Christ himself. Because of Christ, the old Law has become obsolete and a new Law has replaced it. This is why the Jew and the Christian can use the same scripture yet end up with differing interpretations. APPENDIX ONE is a listing of Gospel quotations and allusions in the Dialogue. APPENDIX TWO is a review of the issue of the primary audience of the Dialogue. Here arguments are offered for an audience that is primarily Jewish.